Digital Gaps Influencing the Online Learning of Rural Students in Secondary Education: A Systematic Review - Samane-Cutipa, Virginia A. (2022)
—The digital gaps that were amplified due to the COVID-19 pandemic deepened more in vulnerable areas in different parts of the world. The present work aims to analyze the study of digital gaps that influence online learning of students from rural areas in secondary education, based on a systematic review of the literature. It was developed using the PRISMA methodology, the scientific information was retrieved from the Web of Science and ERIC databases in a period of three months. In the searches it was taken as inclusion criteria; open access, year of publication 2017-2021, English and Spanish language, rural secondary education level and exclusion; articles whose studies were carried out in higher education, in specific areas, related to research policies, evaluation, studies before 2017 and articles from systematic reviews. The results and findings emphasize that digital literacy levels are scarce and limited in terms of the skills developed by students and teachers to achieve digital competencies, in addition to restricted access due to technological, economic, and coverage gaps of families. The conclusions are aimed at strengthening urgent educational policies in addition to the integration of the school curriculum.